Karakteristik Komposit Bioplastik pada Variasi Perbandingan Campuran Pati Gadung (Dioscorea hispida Deenst.) dan Karagenan (Carrageenan) - Wara, Fransiskus Yuven; Hartiati, Amna; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This study aims to determine the effect of the comparison of the mixture of yam starch (Dioscorea hypida D.) and carrageenan on the characteristics of bioplastic composites and on determining the comparison of the mixture of yam starch (Dioscorea hipida D.) and carrageenan (Carrageenan) which gives the best bioplastic composite characteristics. This study used a randomized block design (RBD) with a comparative treatment of the mixture of yam starch and carrageenan as follows (70: 30), (60: 40), (50: 50), (30: 70), (40: 60), Each treatment was grouped into 3 based on the time of making process so that 15 experimental units were obtained. The variables observed in this study were tensile strength, elongation at break, elasticity, swelling thickness and biodegradation time. The results showed that the comparison of the mixture of starch and carrageenan significantly affected the tensile strength, elongation at break, elasticity and did not significantly affect the development of thickness (swelling) and biodegradation time. A ratio of yam tubers starch with carrageenan on 50:50, produces the best yam tuber bioplastics, but does not meet the Indonesian national standard (SNI) with the characteristic tensile strength of 3.60 Mpa, elongation at break of 25.373 ± 0.830%, elasticity of 14.219 ± 0.866 Mpa, swelling of 28.3 ± 1.681%, biodegradation time of 6.667 ± 0.577 days. Keywords: yam starch, carrageenan, composites, bioplastics